Wound healing potential of natural honey in diabetic and non-diabetic wistar rats (2014)
The cutaneous wound healing effects of natural honey were compared in diabetic and non-diabetic rats. Thirty adult male Wistar rats (159g ± 31.5) where randomized into alloxan diabetics (n=15) and non-diabetic (n=15) groups. A 6mm full thickness biopsy punch wound was created on the nape of each rat under 2% xylazine (5mg/kg) and 5% ketamine (35mg/kg) anaesthesia. The wounds were contaminated with Staphylococcus aureus (108 Colony Forming Unit (CFU). Each group was then randomised into three subgroups: A [control, n=5], B (n=5) amikacin (0.8mg) and C (n=5) natural honey (0.1 ml) topical treatments. Wounds were evaluated at day: 3, 5, 7, 9, 11, 13, and 15 for wetness, oedema, hyperemia, granulation tissues, and contraction. Wounds of animals in the diabetic group showed significantly less (p>0.05) wetness compared with the non-diabetic group at days 3-5 (p=0.002) and 5-9, p=0.002 while the amikacin subgroup of the non-diabetic group showed non-significant but notable level of wetness at days 5-7. A significantly (p>0.05) more wound edge oedema was shown by the diabetic than the non-diabetic group at days 3-5 (p=0.000) with the trend being; control > amikacin > honey. The percentage of animals with wound edge oedema between days 3-5 in the non-diabetic group was honey (20%), amikacin (20%) and control (60%); and diabetic group was honey (40%), amikacin (100%) and Control (100%). Between days 5-7, 80% of wounds in both groups where without wound edge oedema except the control subgroups. Wounds of rats in the diabetic group were significantly more hyperaemic (p>0.05) at days 5-9 (p=0.001) and days 9-15 (p=0.000), with the trend being control > amikacin = honey. Wounds of rats in the non-diabetic groups healed with significantly more (p < 0.05) granulation tissues at days 5-9 (p=0.001) (honey = amikacin > control). Control group at days: 5-9 (p=0.001), 9-15 (p=0.000); amikacin at days: 5-9 (p=0.002), 9-15 (p=0.005); and honey at days: 5-9 (p=0.005) and 9-15 (p= 0.001). Differences in wound diameter (a reflection of wound contraction) were not significantly notable in both subgroups (p > 0.05) at various days of measurement except at days 3-5(p=0.008). Honey and amikacin were effective in enhancing cutaneous wounds healing in wistar rats studied. In diabetic rats, honey showed a promising result when compared to amikacin hence honey could be recommended for wound management of diabetic patient in human and animal hospitals